Comunidade Halofítica Herbáceo-arbustiva em Perímetro Irrigado do Município de Pentecoste–CE - Bonilla, Oriel Herrera (2019)
Salinization of soils is a problem that occurs when there is an excess of salts in the soil solution, affecting livestock and agriculture, causing economic and environmental damages. The objective of this work was to evaluate plant communities present in salinized areas of the irrigated perimeter Curu-Recuperação, in Pentecoste-CE. Five collections were carried out in two perimeter areas, in three seasons of the year (beginning of the rainy season, end of the rainy season and dry season), consisting of plant counts and soil collections. The presence of 37 species divided into 14 families was recorded, with Fabaceae being the most representative. The species Blutaparon vermiculare L., Cyperus rotundus L. and Malachra fasciata Jacq., were the most representative, being the first species with the greatest uniformity in the distribution in all collections. The Shannon index obtained was similar to that found in areas under the effect of saline stress. Therefore, it was possible to identify species tolerant to salinity in the soil and with food and medicinal applications, for use in haloforraginculture programs and in the recovery of degraded soils